2022
DOI: 10.1002/bio.4363
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence properties of anodic aluminium oxide films formed in a mixture of malonic acid and oxalic acid

Abstract: In this work, porous anodic aluminium oxide (AAO) films were fabricated by anodization in an electrolyte mixture with various concentration ratios of malonic acid and oxalic acid at room temperature. The photoluminescence (PL) properties of the AAO films before and after annealing from 300°C to 650°C in air or vacuum conditions were investigated, showing a strong PL band in the range 300–550 nm. We observed a weak PL in the AAO film formed in the malonic acid electrolyte, whereas the films fabricated using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Meanwhile, Huang et al [ 27 ] suggested that the PL in AAO membrane originates from oxygen ion defect states (F center) within the AAO membrane, with emission peaks located at 413 nm and 430 nm. The PL effect of AAO has been explored in many studies [ 28 , 29 , 30 , 31 ], among which Zheng et al [ 31 ] investigated the variation in PL intensity of AAO under different anodizing voltages. It was found that the PL intensity of AAO significantly decreases at high voltages of 130 V compared with traditional MA at 40 V [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Huang et al [ 27 ] suggested that the PL in AAO membrane originates from oxygen ion defect states (F center) within the AAO membrane, with emission peaks located at 413 nm and 430 nm. The PL effect of AAO has been explored in many studies [ 28 , 29 , 30 , 31 ], among which Zheng et al [ 31 ] investigated the variation in PL intensity of AAO under different anodizing voltages. It was found that the PL intensity of AAO significantly decreases at high voltages of 130 V compared with traditional MA at 40 V [ 31 ].…”
Section: Introductionmentioning
confidence: 99%